A UTOPIC APPROACH TO THE RELATIONSHIP OF WOMEN WITH TECHNOLOGY: CYBERFEMINISM - Sibel Fügan VAROL (Fırat University, 2019)
Innovations in information and communication technologies have raised the question of whether the technology is gendered. While answers to this question pointed out the male character of technology, some feminists who appeared in the early nineties asserted that technology was essentially female, not male. According to these women who called themselves cyberfeminist, there was a supposed affinity with technology. Although cyberfeminists admit the patriarchal character of industrial technology, they claim that digital technologies have brought about a new relationship between women and machines. This optimistic view of cyberfeminsts may be considered important due to the new perspective it brings to the relationship between technology and gender and the emphasis it places on the opportunities offered by the cyberspace to women. However, the same view is criticised for ignoring the character of the cyberspace that reflect the social inequalities in the real life, therefore for being utopic. This article assumes that cyberfeminism is a movement that should be discussed taking into account such criticisms. Accordingly, the article deals with cyberfeminism in its historical development, starting from its founding texts, and reveals its basic arguments and criticisms against them.